CONTENT, METHODOLOGICAL FEATURES OF THE PREPARATION AND CONDUCT OF ECOLOGICAL EXCURSIONS (ON THE EXAMPLE OF Kryvyi Rih) (Ecological Bulletin of Kryvyi Rih District, 2024)
The greening of thinking and the hedonization of life are processes that have greatly influenced the motives for spending leisure time in recent decades. Ecotourism has become a way of exploring unique and exotic natural landscapes and a tool for their preservation. Such an interpretation of ecotourism deprives residents of large industrial cities, far from such environmental sites, of the opportunity to join the process of ecological cognition. The available sources analyzed by the authors show that the concept of ecological excursions is not developed, which overlaps with ecological tourism, but is aimed at revealing only one aspect of ecology - the problem of protecting natural landscapes within specially protected natural areas/water bodies. The author's interpretation of ecological excursions as a type of industrial and sustainable tourism is broader. Only through understanding the essence of an environmental problem can we find ways to solve it, and during ecological excursions, visitors can directly understand the nature and causes of the environmental crisis, its consequences, offer local solutions to environmental problems, and gain experience in environmental behavior through observation, study, understanding, and research under the guidance of a qualified guide. The authors of the study set out to reveal the essence of the content and methodological features of preparing and conducting excursions. Based on their own many years of experience in excursion activities, the authors substantiated and characterized their own vision of the excursion process related to environmental education and upbringing. The problematic aspects of the existing approach are highlighted and the authors' own vision of the process of developing, organizing and conducting environmental excursions is substantiated. The specific features of each stage of the development of an ecological excursion are identified, and examples of methods from the author's own experience are given.
Keywords: ecological excursion, ecological tourism, sustainable tourism, industrial tourism, method of preparing and conducting excursions.